2014 IEEE International Electron Devices Meeting 2014
DOI: 10.1109/iedm.2014.7047106
|View full text |Cite
|
Sign up to set email alerts
|

High-performance CMOS-compatible self-aligned In<inf>0.53</inf>Ga<inf>0.47</inf>As MOSFETs with GMSAT over 2200 &#x00B5;S/&#x00B5;m at V<inf>DD</inf> = 0.5 V

Abstract: We demonstratehigh-performance self-aligned In 0.53 Ga 0.47 As-channel MOSFETs with effective channel length L EFF down to 20 nm, peak transconductance G MSAT over 2200 μS/μm at L EFF = 30 nm and supply voltage V DD = 0.5 V, thin inversion oxide thickness T INV = 1.8 nm, and low series resistance R EXT = 270 Ω.μm. These MOSFETs operate within 20% of the ballistic limit for L EFF ≤ 30 nm and are among the best In 0.53 Ga 0.47 As FETs in literature. We investigate the effects of channel/barrier doping on FET per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Threshold voltage and Subthreshold swing Vs Gate length characteristics of enhancement mode In 0.7 Ga 0.3 As buried channel MOSFETs are shown in Fig. 4 [167,80]. Yannin Sun et al have been demonstrated the short channel behavior of E-mode In 0.70 Ga 0.30 As buried -channel MOSFETs.…”
Section: Developments In Inp Based Mosfetsmentioning
confidence: 97%
See 3 more Smart Citations
“…Threshold voltage and Subthreshold swing Vs Gate length characteristics of enhancement mode In 0.7 Ga 0.3 As buried channel MOSFETs are shown in Fig. 4 [167,80]. Yannin Sun et al have been demonstrated the short channel behavior of E-mode In 0.70 Ga 0.30 As buried -channel MOSFETs.…”
Section: Developments In Inp Based Mosfetsmentioning
confidence: 97%
“…The threshold voltage and DIBL Vs Gate length characteristics of enhancement mode In 0.7 Ga 0.3 As buried channel MOSFET is shown in Fig. 5 [167,80]. It has been shown that the subthreshold swing and drain induced barrier lowering increases with reduction in gate length and I on /I off also decreases with decreasing Lg which indicates severe short-channel effects for low gate length devices.…”
Section: Developments In Inp Based Mosfetsmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance the process can be simplified and allows for more design flexibility, much lower packaging cost, and most importantly, smaller parasitic device capacitance. Moreover, synergies can be explored between such nanoscale photonic elements and their electronic counterparts, as metal-oxide-semiconductor field-effect transistors that use III–V semiconductors as channel materials are being monolithically integrated on Si as next generation logic devices3.…”
mentioning
confidence: 99%